2022
DOI: 10.3390/jcm11175032
|View full text |Cite
|
Sign up to set email alerts
|

Air-Pressure-Supported Application of Cultured Human Keratinocytes in a Fibrin Sealant Suspension as a Potential Clinical Tool for Large-Scale Wounds

Abstract: The treatment of large-scale skin wounds remains a therapeutic challenge. In most cases there is not enough autologous material available for full coverage. Cultured epithelial autografts are efficient in restoring the lost epidermal cover; however, they have some disadvantages, such as difficult application and protracted cell cultivation periods. Transplanting a sprayed keratinocyte suspension in fibrin sealant as biological carrier is an option to overcome those disadvantages. Here, we studied different see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Therefore, it has been proposed as a potential adjunct treatment in situations where CEAs may be indicated. This suspension spay-on application has been studied in vitro and shown to be a viable option for wound treatment as it produces good confluence and uniform distribution of keratinocytes while keeping the cells undamaged when used in conjunction with a fibrin sealant 60 . This spray-on technique has also been successfully used clinically as a treatment in several large burn cases 61–63 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been proposed as a potential adjunct treatment in situations where CEAs may be indicated. This suspension spay-on application has been studied in vitro and shown to be a viable option for wound treatment as it produces good confluence and uniform distribution of keratinocytes while keeping the cells undamaged when used in conjunction with a fibrin sealant 60 . This spray-on technique has also been successfully used clinically as a treatment in several large burn cases 61–63 .…”
Section: Methodsmentioning
confidence: 99%
“…This suspension spay-on application has been studied in vitro and shown to be a viable option for wound treatment as it produces good confluence and uniform distribution of keratinocytes while keeping the cells undamaged when used in conjunction with a fibrin sealant. 60 This spray-on technique has also been successfully used clinically as a treatment in several large burn cases. [61][62][63] However, this technique still needs more research to understand its capabilities and applicabilities, as it was demonstrated in a retrospective study by Karlsson et al 64 that there was no significant difference in using spray-on keratinocytes in addition to autologous grafting compared with autologous graft alone.…”
Section: Spray-on Technique Of Autologous Keratinocytes In Suspensionmentioning
confidence: 99%
“…Optimally, large amounts of the patient's epidermal cells would be available without distinct donor site morbidity to restore the skin's vital function in cases that do not allow for an autologous transplantation [13]. One possible strategic solution in the preceding cases would be the development of bioprinted constructs containing the patient's own cells as skin substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the proper structural and 3D orientation of the cells and biomaterials, this mimics complex in vivo conditions and facilitates the possible integration of a biofabricated skin graft into Advances in tissue engineering in the past decades have already led to many commercially available mono-or multilayered, biological, and synthetic new skin substitutes. For example, cultured epithelial sheet grafts [15][16][17] by themselves, on carriers, or on suspensions of cultured keratinocytes [13,18] have been integrated into epithelial autografts and successfully used in burn treatment since the early 1980s [18]. Before the advent of bioprinting, various elaborate research models attempted to imitate the natural process of skin reconstitution by combining cell culture techniques with allogenic dermal grafts to mimic 3D skin substitution.…”
Section: Introductionmentioning
confidence: 99%
“…The engineering of three-dimensional (3D) skeletal muscle tissue constructs holds promise for treating volumetric muscle loss without sacrificing healthy donor muscle [ 1 , 2 , 3 ]. In relation to this, the in vivo production of tissue represents a promising option [ 4 , 5 , 6 , 7 ]. Axial vascularization enables a sufficient vascular supply and is therefore essential for the survival of transplanted and engineered tissue [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%